2010
DOI: 10.1111/j.1346-8138.2010.00913.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Malassezia microbiota of healthy subjects differ by sex, body part and season

Abstract: Malassezia is a component of normal cutaneous resident microbiota. The aim of this study was to quantitatively clarify the differences in cutaneous Malassezia microbiota in healthy subjects by sex, body part and season. Samples were collected from the forehead, cheek, upper chest and upper back of 20 healthy men and 20 healthy women (average age 32 years) in summer and winter by the swab method. Malassezia DNA was analyzed using a real-time PCR system. As a result, in sex, body parts and season, men, the upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 24 publications
4
36
2
2
Order By: Relevance
“…There can also be a relationship between the AD-affected body part and the prevalent yeast genera: if Malassezia mostly colonize lipid-rich areas; Candida usually appear on hands and legs. The data obtained in the present study are similar to those from previous studies [10,14,40]. In the child group, the yeast colonization rate was significantly lower than in the adult group.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…There can also be a relationship between the AD-affected body part and the prevalent yeast genera: if Malassezia mostly colonize lipid-rich areas; Candida usually appear on hands and legs. The data obtained in the present study are similar to those from previous studies [10,14,40]. In the child group, the yeast colonization rate was significantly lower than in the adult group.…”
Section: Discussionsupporting
confidence: 82%
“…With regard to non-Malassezia fungi, this finding is not surprising, given that healthy skin forms a physical barrier with many defensive strategies, and that transient or commensal yeasts from the environment are incapable of surviving on an intact skin for long periods of time. Malassezia yeasts are members of the normal human cutaneous flora and are found on the skin of healthy adults [9,40]. In the present study, we observed no Malassezia growth in the control group and, in general, colonization with these yeasts was very low as compared with other studies.…”
Section: Discussioncontrasting
confidence: 41%
“…from female patients was caused by a lot of sebum in the acne patients. In addition, Akaza et al [26] reported that the total number of Malassezia spp. from the face of healthy male subjects was significantly greater than that from healthy female subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In all, no significant differences were observed between the bacterial communities of males and females regardless of age group. Moreover, a study comparing the levels of Propionibacterium and coagulase negative Staphylococcus in middle-aged men and women found no significant differences at the forehead, cheek, upper chest, or back [33]. However, it was found that males harbored greater total amounts of the fungi Malassezia .…”
Section: Host Factors and The Skin Microbiotamentioning
confidence: 99%